2017
DOI: 10.3390/ijerph14010096
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Violence against Health Care Workers in North Chinese Hospitals: A Cross-Sectional Survey

Abstract: This research aimed to determine the prevalence of workplace violence (WPV) against healthcare workers, explore the frequency distribution of violence in different occupational groups, and determine which healthcare occupation suffers from WPV most frequently. Furthermore, the current study aimed to compare risk factors affecting different types of WPV in Chinese hospitals. A cross-sectional design was utilized. A total of 1899 healthcare workers from Heilongjiang, a province in Northeastern China, completed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
82
3
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(122 citation statements)
references
References 20 publications
14
82
3
6
Order By: Relevance
“…15 A good number of previous publications have mentioned the consequences of HCWPV which is coming up as a new occupational health hazard and has significant long-lasting effect on HCPs. 1,3,11,13,[22][23][24][25][26] Some of these are lower morale, anger, loss of confidence, burnout, time off work, disability and change in job status etc. 44 Each incident affects a number of staff members.…”
Section: Consequencesmentioning
confidence: 99%
See 2 more Smart Citations
“…15 A good number of previous publications have mentioned the consequences of HCWPV which is coming up as a new occupational health hazard and has significant long-lasting effect on HCPs. 1,3,11,13,[22][23][24][25][26] Some of these are lower morale, anger, loss of confidence, burnout, time off work, disability and change in job status etc. 44 Each incident affects a number of staff members.…”
Section: Consequencesmentioning
confidence: 99%
“…22,24,26 There is a circular relationship between psychological stress and HCWPV; violence causes anxiety and stress; anxious and stressed HCPs are prone to exposure to violence. [22][23][24] Fear, anxiety and agony undoubtedly have profound physical mental and social consequences as these can impair victims' quality of life, influence their job performance, affect patient safety, and lead to changes in immune system functioning. Other serious consequences for HCPs are increased occupational strain, need for medical treatment, lost workdays and absenteeism, employment termination or turnover, disability and even death.…”
Section: Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Workplace violence is one of the most significant psychosocial work hazards and a growing occupational safety and health concern in health care settings (Cheng & Pien, ; Lanctôt & Guay, ; Parent‐Thirion et al., ; Sun et al., ; Zhang et al., ). Workplace violence is defined as any incident where staff are abused, threatened or assaulted in circumstances related to their work.…”
Section: Introductionmentioning
confidence: 99%
“…Among workers in various occupations, nurses were found to be one of the high‐risk occupational groups for workplace violence and work‐related mental distress (Cheng & Pien, ; Occupational Safety and Health Administration, ; Parent‐Thirion et al., ; Pien, Cheng, Chen, & Chen, ). Studies from other Asian countries have indicated that nurses are at alarmingly high risk for workplace violence, with a one‐year prevalence ranging from 25.8% to 95.5% (Cheung & Yip, ; Choi & Lee, ; Sun et al., ; Zhang et al., ). However, few studies examined the impact of organisational psychosocial safety climate on workplace violence and workers’ health (Courcy, Morin, & Madore, ; Lee, Kim, & Park, ; Sun et al., ), and only two studies have used PSC scale in the Asian population (Idris & Dollard, ; Idris et al., ).…”
Section: Introductionmentioning
confidence: 99%